Mysticism in Urdu Poetry of the Poets of District Ghotki - Khokhar, Talib Hussain (sourcecoder, 2023)
It takes a great deal of history to produce a little literature. Therefore, there are a few people in this world who master this art. These people may belong to any part of the world. It is not only the domain of developed countries but also developing countries like Pakistan excel in this field as well. The provinces and cities of Pakistan are brimming with people who have contributed to the field of literature. Same is the case with Ghotki, one of the oldest cities of Pakistan. It has produced people with great imagination and Innovation in the field of Urdu literature. People like Maulan Baha-ud-din Bahae, Sufi Muhammad Fakeer Ghoto, Sufi Fakeer Anwar Ali Shah, Fakeer Sobha Laghari, Syed Sattar Dino Shah, Fakeer syed Hazoor Bux Shah, et al, are beacons of light in this regard. The purpose of this study is to let people know how these said individuals of Ghotki have left no stone unturned in the field of Urdu literature, both Poetry and Prose. The purpose of their writing was to spread the message of brotherhood among the diverse inhabitants of Ghotki.